Sonogashira Coupling (Cu/Amine‐Free) of ArBr/Cl in Aerobic Condition and N‐Benzylation of Aniline with Benzyl Alcohol Catalyzed by Complexes of Pd(II) with Sulfated/Selenated NHCs. Issue 10 (11th March 2020) - Dubey, Pooja; Singh, Ajai K.
Abstract: The moisture and air insensitive, and thermally stable [Pd(L1/L2 ‐H)Cl][PF6 ] (1 /2 ) and [Pd(L3 /L4 ‐HI)Cl2 ] (3 /4 ) catalyze N ‐benzylation of aniline (at 100 °C) and Sonogashira coupling of ArBr/Cl (at 80 °C) in the presence of KOH and K2 CO3 respectively. The optimum catalyst loading (mol %) is 0.02‐0.1 for the C−C coupling and 0.5 for N ‐benzylation. The 1–4 were found reusable. The L1 /L2 =3‐(1‐benzyl‐1 H ‐1, 2, 3‐triazol‐4‐yl)methyl)‐1‐(2‐(phenyl thio/seleno)ethyl)‐1 H ‐benzo[d]imidazol‐3‐ium hexafluorophosphate and L3 /L4 = 4‐methyl‐1‐(2‐(phenylthio/seleno)ethyl)‐1H‐1, 2, 4‐triazol‐4‐ium iodide are precursors of N ‐heterocyclic carbenes. Copper‐catalyzed click reaction gave L1 /L2 . The treatment of triazole with ClCH2 CH2 Cl, [PhS/Se] − Na + and MeI successively afforded L3 /L4 . The sequence of reactions of L1 ‐L4 with Ag2 O and [Pd(CH3 CN)2 Cl2 ] (M : L=1 : 1) gave 1–4 . The L1‐L4 and 1–4 were characterized by elemental analyses, multi‐nuclei NMR, HR‐MS and single‐crystal structure (3 and 4 ). The geometry of Pd in 3 /4 is nearly square planar. The bond distances (Å) in 3 /4 are: Pd−S/Se, 2.3040(7)/2.402(2) and Pd−C, 1.961(3)/1.938(11). Abstract : Pd(II) complexes of selenated/sulfated NHCs catalyze N ‐alkylation/Cu‐amine‐free Sonogashira coupling of ArBr/Cl (optimum loading 0.5 /0.02‐0.1 mol%) and remain active upto 9‐cycles for both the reactions. The catalytic activity of Pd complexes having tridentate ligands somewhat higher than than Pd complexes formed with bidentate ligands. Moreover, complexes of thioethers are produce slightly higher yields than those of selenoethers. The tentative mechanisms for both the catalytc processes are described.